Odpowiedzi

2009-10-12T23:04:38+02:00
A)(3/2x-1/10)(3/2x+1/10)
b)(9ab-1)(9ab+1)
c)(5x+3y-5)(5x+3y+5)
d)(a-9b-a²b)(a-9b+a²b)
e)(5x-x-y)(5x+x+y)
f)(10-3x-7y)(10+3x+7y)
g)(a+2b-3c-4d)(a+2b+3c+4d)
h)(2x+3-x+1)(2x+3+x-1)=(x+4)(3x+2)
(2x+1)²
j)(3a-1)²
k)(7x-5y)²
l)(a-b)²-25=(a-b-5)(a-b+5)
ł)1-(a+b)²=(1-a-b)(1+a+b)
m)(8-2y)³
n)(a+6)³
1 4 1
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-10-12T23:14:00+02:00
A) (9/4)x²-1/100=((3/2)x-1/10)((3/2)x+1/10)

b) 81a²b²-1=(9ab-1)(9ab+1)

c) (5x+3y)²-25=((5x+3y)-5)((5x+3y)+5)=(5x+3y-5)(5x+3y+5)

d) (a-9b)²-a⁴b²=((a-9b)-a²b)((a-9b)+a²b)=(a-9b-a²b)(a-9b+a²b)

e) 25x²-(x+y)²=(5x-(x+y))(5x+(x+y))=(5x-x-y)(5x+x+y)=(4x-y)(6x+y)

f) 100-(3x+7y)²=(10-(3x+7y))(10+(3x+7y))=(10-3x-7y)(10+3x+7y)

g) (a+2b)²-(3c+4d)²=((a+2b)+(3c+4d))((a+2b)-(3c+4d))=(a+2b+3c+4d)(a+2b-3c-4d)

h) (2x+3)²-(x-1)²=((2x+3)+(x-1))((2x+3)-(x-1))=(2x+3+x-1)(2x+3-x+1)=(3x+2)(x+4)

i) 4x²+4x+1=(2x+1)²
(2x+1)²=(2x)²+2*2x*1+1²=4x²+4x+1

j) 9a²-6a+1=(3a+1)²
(3a+1)²=(3a)²+2*3a*1+1²=9a²+6a+1

k) 49x²-70xy+25y²=(7x-5y)²
(7x-5y)²=(7x)²-2*(7x)*(5y)+(5y)²=49x²-70xy+25y²

l) a²-2ab+b²-25=(a-b)²-25=((a-b)-5)((a-b)+5)=(a-b-5)(a-b+5)
(a-b)²=a²-2ab+b²

ł) 1-a²-2ab-b²=1-(a+b)²=(1-(a+b))(1+(a+b))=(1-a-b)(1+a+b)
(a+b)²=a²+2ab+b²

m) 125x³+75x²+15x+1=(5x+1)³
(5x+1)³=(5x)³+3*(5x)²*1+3*5x*1²+1³=125x³+75x²+15x+1

n) 64-96y+48y²-8y³=(4-2y)²
(4-2y)³=4³-3*4²*2y+3*4*(2y)²-(2y)³=64-96y+48y³-8y³

o) a³+18a²+108a+216 = (a+6)³
(a+6)³=a³+3*a²*6+3*a*6²+6³=a³+18a²+108a+216
1 5 1